Ijtihad Dalam Sejarah dan Perkembangannya Hingga Masa Kontemporer (Prodi Hukum Ekonomi Syariah STAIN Teungku Dirundeng Meulaboh, 2020)
Ijtiha>d which has been outlined by the Prophet Muhammad in his time, then sued the Shahabah after the Prophet saw. died to solve problems that occur in society that are not directly explained in the al-Quran and continuing to the present day as an effort to formulate a systematic law is the path taken to install syaria law in various issues that arise. The development of ijtiha>d in history until now needs to be used as a comparison material to see the model of ijtiha>d in its time to the existence of taqlid in it. As we know that fiqh is a flexible science that can develop along with the times, places, conditions, and customs. So that the mujtahid until now must be able to solve problems that arise. The explanation in this article finds that there is continuity and discontinuity between ijtiha>d and taqlid as well as the new ijtiha>d model which is limited to the respective Imam of mazhab which is happening nowadays in the form of ijtiha>d intiqa'i and also a new models of ijtiha>d for which there is no previous opinion or named as ijtiha>d insya'i.